Records of the South Carolina General Assembly - South Carolina. General Assembly
Letter (undated) to the assembly from an unknown writer relating to the abolition of the legislative council; letter (undated) to the president and members of the senate relating to the custom of dueling; and photocopy of a letter (1787) signed by members of the assembly and addressed to the to U.S. Congress relating to the boundary between North Carolina and South Carolina.
In part, negative photocopy.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Congress -- Correspondence; Dueling -- South Carolina; North Carolina -- Boundaries -- South Carolina; South Carolina -- Boundaries -- North Carolina; South Carolina -- Politics and government -- 1775-1865.